2003
DOI: 10.1097/00004032-200310000-00004
|View full text |Cite
|
Sign up to set email alerts
|

AGE DEPENDENCIES OF 90Sr INCORPORATION IN DENTAL TISSUES: COMPARATIVE ANALYSIS AND INTERPRETATION OF DIFFERENT KINDS OF MEASUREMENTS OBTAINED FOR RESIDENTS ON THE TECHA RIVER

Abstract: Human teeth have been considered as dosimeters for decades. Methods include the in vivo measurement of 90Sr/90Y in teeth with a tooth-beta counter, the radiochemical determination of 90Sr in whole teeth, and the measurement of dose in teeth by use of electron paramagnetic resonance. Presented in this paper are results of 2,514 tooth-beta counter measurements, 334 radiochemical measurements, and 218 electron paramagnetic resonance measurements for residents living in settlements along the Techa River. All three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Blanchard 1966, Leggett et al 1982, Mangano et al 2003, Odum 1957, Papworth and Vennart 1984, Rickard 1964, Tolstykh et al 2003, Vose and Koontz 1959, Yamaguchi et al 2007). These studies provide much of the fundamental knowledge necessary for archaeological investigations of human mobility using strontium isotopes.…”
Section: Accepted For Publication In the Annals Of Human Biology 2010mentioning
confidence: 99%
“…Blanchard 1966, Leggett et al 1982, Mangano et al 2003, Odum 1957, Papworth and Vennart 1984, Rickard 1964, Tolstykh et al 2003, Vose and Koontz 1959, Yamaguchi et al 2007). These studies provide much of the fundamental knowledge necessary for archaeological investigations of human mobility using strontium isotopes.…”
Section: Accepted For Publication In the Annals Of Human Biology 2010mentioning
confidence: 99%
“…Loss of minerals from tooth enamel is attributed mainly to ion diffusion and tooth surface reactions. Strontium elimination is likely to occur by the same processes as those affecting calcium elimination, i.e., diffusion, surface dissolution or demineralisation and mechanical attrition (Suga and Watabe, 1992 ;Tolstykh et al, 2003).…”
Section: Epr Response Of Tooth Enamel To Doses From Internal β β β β-mentioning
confidence: 99%
“…These factors make the volume-averaged dose provided by EPR measurements of little significance for short-range particles. Tolstykh et al (2000Tolstykh et al ( , 2003 argued against the suitability of EPR dosimetry with 90 Sr contaminated teeth, in particular because the estimate of the tooth enamel dose should account for the time dependence of the 90 Sr content and distribution not only in enamel, but also, and especially, in dentine. They concluded that EPR tooth enamel dosimetry should be limited to the assessment of the external dose component.…”
Section: Epr Response Of Tooth Enamel To Doses From Internal β β β β-mentioning
confidence: 99%
See 2 more Smart Citations